Dancing Into Oblivion: The Pilipino Cultural Night and the Narration of Contemporary Filipina/o America - Gonzalves, Theodore S. (Archīum Ateneo, 2024)
How have performances developed by Filipino Americans over the twentieth century conveyed important lessons about culture, nation, and community? In other words, what do Filipino American cultural performances have to say about the formation of “national identity” and “community”? I select three contexts to highlight these changes: the postindustrialization of the US economy; the reaction to race, taxes and education in the Bakke vs. UC Board of Regents decision; and the political realignment of the Reagan democrats. We see the continued immigration of Filipino so-called “professional” families to the United States. Their children seek senses of themselves amidst attacks on ethnic studies, affirmative action, and the presence of immigrants in California. And here the Pilipino Cultural Night (PCN) as a performance genre emerges. For the thousands of young Filipino Americans who have taken to the stage or for those who felt more comfortable in the wings, participating in these shows has been some of the only history lessons available about the Philippine revolution of 1896, the literary politics of Carlos Bulosan, the struggle of Ilocano and Visayan farm workers in Hawaii, the back-breaking labor in Salinas, Delano, Spokane, or Chicago. They also turn their attention to the Philippines and to the outer diaspora, learning of the plight of overseas workers like Flor Contemplacion and the devastation of the archipelago’s natural resources. At the end of the twentieth century, performing a play or choreographing dances offers not only the possibility of entertainment, but also the chance to tell stories about the past, to call a community into being, to convey youthful insecurities, or to raise oblique and ambivalent critiques of the America they provisionally call home. Cultural performances such as the PCN assume the burden of providing a “performative transcript” of who Filipino Americans are. With the dominant historical record so heavily biased toward professionals’ and elites’ accounts of the past, ordinary folks have often turned to the field of culture to symbolically enact what would not be possible elsewhere. But ordinary folks are not the only ones to recognize the power and dynamism of the terrain of culture. We already know that the powerful remind the rest of us of who they are, what they supposedly do, and why they deserve such an elevation station. In that alternative to the dominant historiography, we find oblique and sometimes parallel responses to the existing and oftentimes unquestioned written record.